Cross-Border financial effects of global warming - Emilio Carnevali; Matteo Deleidi; Riccardo Pariboni; Marco Veronese Passarella (University of Massachusetts, Department of Economics, 2019)
We develop an ecological open-economy SFC model that enables testing cross-area interactions among productive sectors, financial markets and the ecosystem. We show that the unequal technical progress across areas, coupled with rising ecological awareness, can force governments of less ecologically efficient areas to move further away from low-carbon assets. We argue that "green" monetary and fiscal policies can be used to tackle climate change and financial instability. However, their effectiveness depends crucially on the impact of cross-border financial flows and growth rate differentials on exchange rates. Without a cross-area policy coordination plan, currency fluctuations can bring about unintended consequences, undermining green policies' effects.
Keywords: D53; E44; F37; G17; Q54; 330; Stock-Flow Consistent Models; Climate Change; Financial Stability